COMPARATIVE ANALYSIS OF PEDAGOGICAL VIEWS OF H. SKOVORODA AND R. STEINER - Іонова, Олена (New Collegium, 2020)
The article presents the comparative analysis of pedagogical views of H. Skovoroda and R. Steiner. The author reveals the spiritual affinity and consonance of views of these thinkers and educators in such main aspects: synthesis of human values of truth, goodness and beauty as a foundation of human education; ideal of anthropological universalism. The latter forms the image of a man as the microcosm which reflects the macrocosm, considers human individuality to be the unity of the spiritual, mental and physical being, pro- vides understanding of education as a process of revealing each person’s true vocation («natural affinity») to certain kind of activity and requires the holistic development of a child, his «head, heart and hands». The author makes the conclusion that Steiner-pedagogy fits well into context of Ukrainian cultural tradition.